Naphthalimide‐Containing Isomeric Urea Derivatives: Mechanoluminescence and Fluoride Recognition. Issue 11 (21st September 2017) - Devi, Kakali; Sarma, Rupam J
Abstract: Isomeric ortho, meta and para naphthalimide–urea derivativesND‐2U, ND‐3U andND‐4U were synthesized and characterized. Upon gentle mechanical stimulation, the weakly emissive ortho isomeric sampleND‐2U was transformed into a yellow‐green emissive material ( λ em =500 nm), with Δ λ ≈125 nm. The mechanoluminescent emission of this isomer could be "switched off" by exposing the sample to solvent vapour. Moreover, ND‐2U could respond to fluoride anions in solution with a dramatic enhancement of fluorescence at λ =446 nm. The sigmoidal nature of the binding isotherm suggested cooperative binding of fluoride to the ortho  isomer. 1 H NMR spectroscopic studies provided vital insights into the nature ofND‐2U /F − complexation, highlighting the role of the proximal 1, 8‐naphthalimide motif. Abstract : The daily grind : The mechanoluminescent behaviour of naphthalimide‐containing urea derivatives varies depending on the isomeric linkage positions. The geometrically constrained ortho  isomer shows reversible mechanoluminescent switching with Δ λ ≈125 nm in the solid state. Moreover, in solution the isomer recognises fluoride anions with distinct cooperativity, characterised by a sigmoidal binding isotherm.